Aktuelle Fragen des Bank- und Kapitalmarktrechts I: Non-Performing-Loans/Faule Kredite - Handel, Work-Out, Outsourcing und Securitisation - Dietmar Anders; Andreas Binder; Ralf Hesdahl; Christoph Schalast; Thomas Thöne (Hochschule für Bankwirtschaft (HfB), 2004)
The report deals with the current legal questions relating to the trading, working out and outsourcing of non-performing loans. Within this framework the basic legal provisions and the problems arising therefrom, for example, in the area of data protection or banking secrecy, are explained and practical suggestions for a proposed line of action are made. The solutions range from the classical working out in banks over the new concept of a bad bank to legally complex conception, such as securitisation. The objective is to identify the basic lines taken in the discussion so far and to pinpoint the approaches for a continued development of the topic for the purposes of research and legal practice.
urn:nbn:de:101:1-20080724125
Keywords: K12; K19; K22; K29; 330; Non-Performing-Loans; Distressed Debt Trading; Bad Bank; Work-Out; Outsourcing; Securitisation; Data Protection; Bankers duty of secrecy; True Sale; Asset-Backed Securities